Cell invasion by Neisseria meningitidis requires a functional interplay between the Focal adhesion kinase, Src and Cortactin - Slanina, Heiko; Hebling, Sabrina; Hauck, Christof R.; Schubert-Unkmeir, Alexandra (My University, 2012)
Entry of Neisseria meningitidis (the meningococcus) into human brain microvascular endothelial cells (HBMEC) is mediated by fibronectin or vitronectin bound to the surface protein Opc forming a bridge to the respective integrins. This interaction leads to cytoskeletal rearrangement and uptake of meningococci. In this study, we determined that the focal adhesion kinase (FAK), which directly associates with integrins, is involved in integrin-mediated internalization of N. meningitidis in HBMEC. Inhibition of FAK activity by the specific FAK inhibitor PF 573882 reduced Opc-mediated invasion of HBMEC more than 90%. Moreover, overexpression of FAK mutants that were either impaired in the kinase activity or were not capable of autophosphorylation or overexpression of the dominant-negative version of FAK (FRNK) blocked integrin-mediated internalization of N. meningitidis. Importantly, FAK-deficient fibroblasts were significantly less invaded by N. meningitidis. Furthermore, N. meningitidis induced tyrosine phosphorylation of several host proteins including the FAK/Src complex substrate cortactin. Inhibition of cortactin expression by siRNA silencing and mutation of critical amino acid residues within cortactin, that encompass Arp2/3 association and dynamin binding, significantly reduced meningococcal invasion into eukaryotic cells suggesting that both domains are critical for efficient uptake of N. meningitidis into eukaryotic cells. Together, these results indicate that N. meningitidis exploits the integrin signal pathway for its entry and that FAK mediates the transfer of signals from activated integrins to the cytoskeleton. A cooperative interplay between FAK, Src and cortactin then enables endocytosis of N. meningitidis into host cells.
Keywords: 570